Urban green spaces and flood disaster management: toward sustainable urban design - Na Liu; Fang Zhang (Frontiers in Public Health)
This paper explores how rapid urbanization and frequent extreme rainfall affect urban flood risk, highlighting that stormwater management challenges worsen due to increased impervious surfaces, altered urban hydrological cycles, and damaged natural retention systems. This paper, grounded in sustainable urban design principles, underscores the significance of green infrastructure for bolstering urban flood resilience. Urban green spaces not only reduce surface runoff through natural storage and infiltration but also improve water quality, regulate urban microclimate, and enhance biodiversity. Furthermore, this paper examines the application of green infrastructure in stormwater management, drawing inspiration from international success stories such as the Amsterdam Canal Network, Singapore’s ABC Waters Program, and Kazan’s “Resilient Belt” project. The study suggests that an integrated “blue-green-gray” strategy, which combines natural ecosystems with engineered facilities, should be adopted to optimize stormwater management efficiency. Despite the significant advantages of green infrastructure, there are still challenges in scaling up the application, connecting decentralized green spaces, and integrating real-time monitoring systems for dynamic regulation. Future research should focus on the synergistic effects of green infrastructure at different urban scales and explore a balanced path between urban expansion and ecological sustainability.